A Social Enterprise, Better Maternal Health Services Through Mobile Messages Automated-System, A Pilot Study in AIC Kijabe Hospital, Kiambu County. - Gichimu, Jacob C.; Adam, Mary; Nyatigo, Fanice (Machakos University, 2018)
There is a tremendous need to increase patient specific approaches to reduce barriers to care and enhance compliance of healthier strategies for pregnant women. Digital innovation is a text messaging platform allowing individually targeted gestation, appropriate health information delivered directly to pregnant women and household level decision-makers. To test technical feasibility and client acceptability; MamaTips was founded in 2016 as free messaging subscription service promoting healthier pregnancy and delivery in a Kenyan context. MamaTips sends health messages through automated-system to enrolled pregnant women in English/Swahili that corresponded to their gestation week for 6 months; educating them on living healthy, pregnancy danger signs and preparedness for safe delivery, leveraged by high mobile phone penetration in Kenya. MamaTips built on work done by Mobile Alliance for Maternal Action (MAMA) adapting and implementing health messaging approach in Kenya targeting women in rural and semi-urban settings. Health-oriented text messages of 160 characters were contextualized by Medical and nutrition experts from Kijabe Hospital and Participants were recruited from outpatient antenatal clinic in Kijabe Hospital. Out of 40 women invited 37 enrolled; 97% participated through the study or until they delivered (N=36), 90% shared messages (47% orally, 21% forwarded and 32% read through recipients’ phones). 95% would re-enrol and recommend others. 74% would pay for such services if re-enrolled for average of Ksh 86. Language appropriateness was 100%. The study identified technical problems with 66% receiving all messages each week, but once identified solutions resulted to all messages being delivered. MamaTips successfully delivered individualized gestational appropriate series of health messages this exhibited desirable and potential to develop a financially sustainable platform through subscription service. Keywords: Automated-system, m-Health, Maternal Health, Digital Innovation, Social Enterprise
Keywords: Maternal Health